Cardiovascular status and echocardiographic changes in survivors of COVID-19 pneumonia three months after hospital discharge - D. V. Krinochkin; E. I. Yaroslavskaya; N. E. Shirokov; E. P. Gultyaeva; I. R. Krinochkina; I. O. Korovina; A. V. Mamarina; N. A. Osokina; N. N. Melnikov; T. A. Trifanova; E. A. Gorbatenko; T. I. Petelina (Российский кардиологический журнал)
Coronavirus disease 2019 (COVID-19) affects the function of all organs and systems. Today, studying the effect of COVID-19 on cardiovascular system, including on echocardiographic characteristics, is relevant.Aim. To study the prevalence of symptoms, cardiovascular disease and changes in echocardiographic data in persons after documented COVID-19 pneumonia 3 months after discharge from the hospital.Material and methods. The study included 106 patients after documented COVID-19 pneumonia. The patients underwent a comprehensive examination during hospitalization and 3 months±2 weeks after discharge from the hospital. The mean age of participants was 47±16 years (19-84 years); 49% of subjects were women.Results. Three months after hospital discharge, the symptoms persisted in 86% of examined patients. There were significant echocardiographic changes as follows: a decrease in LV end-diastolic, end-systolic and stroke volume (113,8±26,8 ml vs 93,5±29,4 ml; 37,7±13,0 ml vs 31,3±14,2 ml; 77,2±17,8 ml vs 62,2±18,7 ml, respectively, p<0,001 for all). The right ventricular anteroposterior dimension and the pulmonary trunk diameter decreased over time (26,0 [24,0-29,3] mm vs 25,0 [23,0-27,0] mm, p=0,004; 21,7±3,6 mm vs 18,7±2,5 mm, p<0,001), the same as the pulmonary artery systolic pressure, estimated by tricuspid regurgitation gradient (28,0 [25,0-32,25] mm Hg vs 21,5 [17,0-25,0] mm Hg). The right atrial volume (42,0 [37,0-50,0] m><0,001), the same as the pulmonary artery systolic pressure, estimated by tricuspid regurgitation gradient (28,0 [25,0-32,25] mm Hg vs 21,5 [17,0-25,0] mm Hg). The right atrial volume (42,0 [37,0-50,0] ml vs 31,0 [22,0-36,5] ml, p<0,001) a><0,001) and maximum width (36,1±4,6 mm vs 34,5±6,5 mm, p=0,023) decreased, while the right atrial maximum length increased (46,7±6,8 mm vs 48,6±7,1 mm, p=0,021).Conclusion. In survivors of COVID-19 pneumonia three months after hospital discharge, complaints persisted in 86% of cases. Cardiovascular diseases were detected in 52% of participants, including hypertension in 48,1% and coronary artery disease in 15,1%. Compared with in-hospital data, the echocardiographic characteristics improved, which was expressed mainly in a decrease in right heart load.